Participatory water institutions and sustainable irrigation management: evidence and lessons from West Bengal, India. Issue 4 (22nd April 2022) - Chattopadhyay, Soumyadip; De, Indranil; Mishra, Prabhat; Parey, Akhilesh; Dutta, Subhasish
Abstract: Based on a survey of selected Water Users' Associations (WUA) and their members in West Bengal, India, this paper examines the nature and determinants of member participation in irrigation management. WUA meetings were held on a regular basis with higher member participation under Tube Well, Check Dam and River Lift Irrigation schemes. Their physical characteristics (e.g., high sub-surface storage and flowing rivers with large catchment areas) and system features (e.g., centralized pump house and defined distribution infrastructure) contribute to better water availability, incentivizing the members to participate. Our regression analysis suggests that along with these factors, the socioeconomic attributes of members and their perception about the functioning and decision making of the WUA influence participation in the collective management of schemes. The more the members perceive the functioning of WUAs as democratic and transparent, the greater is their incentive to participate. Greater participatory involvement of the members in the form of donating land for irrigation construction and in training programs is also found to be crucial. So, this paper argues for making the decision-making processes within WUAs democratic and transparent, along with greater efforts toward capacity building of the members, including training for skill enhancement, management and provision of agricultural support practices. HIGHLIGHTS: Members participate frequently in association meetings in schemes with better water availability. Participation in crop plans and water mapping is limited. Democratic and transparent functioning of associations incentivizes members' participation. Skill development and improved agricultural practices positively influence participation. Members' involvement in maintenance works and land donation facilitates participation.